Empire, migration and identity in the British World - Fedorowich, Kent, 1959-; Thompson, Andrew S. (Andrew Stuart), 1968- (Book collections on Project MUSE., 2013)
This volume brings together established scholars with a new generation of migration and transnational historians. Their work weaves together the 'new' imperial and the 'new' migration histories, and explores the interplay of migration within and between the local, regional, imperial, and transnational arenas.